PENGARUH PERENCANAAN PAJAK DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN - Samsinar, Ade; Sembiring, Evi Dora; Handayani, Novi; Susilawati, Deti; Ekanindya, Ria (Gapenas Publisher, 2024)
This study aims to analyze the influence of tax planning and company size on profit management in manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. The method used a quantitative approach with regression analysis to test the relationship between variables. Data was obtained from the company's annual financial statements which were analyzed using purposive sampling. The results of the study show that tax planning has a significant effect on profit management, where companies with better tax planning tend to practice profit management to achieve certain financial goals. Company size was also found to have a positive relationship with profit management, indicating that large-scale companies tend to be more cautious in reporting profits to maintain investor reputation and trust. This research contributes to investors, academics, and companies in understanding the dynamics of profit management, as well as being a reference in decision-making related to tax policies and financial reporting. So this study also emphasizes the importance of transparency and accountability in the preparation of financial statements to avoid negative impacts on profit management practices